Expression and inducibility of cytochrome P450s in human hepatocytes isolated from chimeric mice with humanised livers. (3rd June 2019) - Uehara, Shotaro; Higuchi, Yuichiro; Yoneda, Nao; Yamazaki, Hiroshi; Suemizu, Hiroshi
Abstract: The evaluation of drug-mediated cytochrome P450 (P450) induction using human hepatocytes is important for predicting drug interactions. In this study, we prepared hepatocytes from chimeric mice with humanised livers (Hu-Liver mice) and evaluated the expression and inducibility of P450s in these hepatocytes. Up to 95% of the Hu-Liver cells stained positive for human leukocyte antigen and the mean viability exceeded 85% ( n  = 10). Monolayer-cultured Hu-Liver cells displayed a similar morphology to cultures of the corresponding human hepatocytes used as transplantation donors. The mRNA expression levels in Hu-Liver cells of 16 P450 forms belonging to P450 subfamilies 1–4 correlated well with the expression levels of the same enzymes in human hepatocytes. The variations in individual P450 mRNA levels between Hu-Liver cells and the corresponding human hepatocytes were within five-fold for 13 P450 forms. The production of 6β-hydroxytestosterone in Hu-Liver cells was significantly increased ( p  < .05) following treatment with the CYP3A inducer, rifampicin. Hu-Liver cells have characteristics similar to those of human hepatocytes in terms of mRNA expression levels and the inducibility of the various P450 forms. Thus, Hu-Liver cells can potentially be used for in vitro drug-mediated induction assays of human hepatic P450s.